Faunistic relations between the ranges of the Eastern Arc mountains: relocation of Peronura hildebrandtiana Karsch, 1889 (Tettigoniidae: Phaneropterinae), the description of the male and implications from its phylogeographical pattern - Hemp, Claudia (Zootaxa, 2011)
P. hildebrandtiana Karsch, 1889 was relocated in the Taita Hills of Kenya. To present only the single female holotype was known. Male and female specimens of this species were found along forest edge in herbaceous vegetation in the Ngangao forest reserve. Closest relative of P. hildebrandtiana Karsch is P. uguenoensis Hemp restricted to the North and South Pare mountains. P. hildebrandtiana is re-described and the male newly described in this paper. Ecological information is provided and co-occurring Saltatoria species listed. Faunistic similarities in flightless Saltatoria between the Taita Hills and the South Pare mountains are discussed.